Tipe dan Gaya Kepemimpinan Kepala Sekolah Dalam Pendidikan - Miftahul Husna; Fadhila Yunita; Bunga Surya Rezeky (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2022)
This study aims to determine the effect of the type and leadership style of school principals in education today. The method used by the researcher in this research is the method of literature study or literature study, where this research method has the aim of collecting material from previous research including journals, articles, books and so on related to the title of this journal and then drawn into a conclusion and poured into in this journal. The results of the literature study of the influence of the type and leadership style of the principal in education greatly affect the level of teacher performance in providing learning, the work productivity of members and the leadership style are well established and planned, where if the leadership style is good, the better the work productivity of members